The ill definition of counter terrorism measures and its consequences on migration - Austrups, Markuss (Riga Graduate School of Law, 2024)
This paper examines the dynamics of counter-terrorism measures and its intersection with migration policies, with a primary focus on the United States and the European Union. This paper further delves into the lack of an internationally agreed-upon definition of terrorism, which leads to diverse interpretations and measures among states. Through the analysis of US’ response to the September 11 attacks the paper describes the development of these interpretations and measures. This paper also analyses the impact of counter-terrorism and security measures in countries of France and Italy, while also doing a case study on cases of the European Court of Human rights and the Supreme Court of the United States of America. The research also underscores the growing association with security threats and migrants, especially Muslim and Arab migrants. Overall this paper uses doctrinal research to find links and patterns of how western countries interpret these measures and how they impact migration and human rights.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Counter-terrorism; Terrorism; Migration